The Influence Of Price, Service Quality, And Physical Environment Towards Customer Loyalty At Salon Industry - Putri, Fenina Berliana; Lestari, Wiwin; Mulyasari, Suci (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
The rapid development of the beauty industry in Indonesia has led to intense competition among salons, making customer retention a critical issue in sustaining business growth. This study aims to analyze the influence of price, service quality, and physical environment on customer satisfaction and its subsequent effect on customer loyalty in the salon industry, with a specific focus on Fenina Salon & Reflexology in Cikarang. Utilizing a quantitative research method, data were collected through an online questionnaire employing a 7-point Likert scale and analyzed using Structural Equation Modeling (SEM) via Smart PLS 4. A total of 121 valid responses were used. The findings reveal that customer satisfaction strongly and significantly influences customer loyalty. Both price and physical environment significantly affect satisfaction, whereas service quality does not show a statistically significant impact. These results indicate that while competitive pricing and a pleasant physical setting enhance satisfaction, perceived service quality alone may not drive it in this context. This study concludes that customer satisfaction acts as a key mediator between operational factors and loyalty. The insights emphasize the importance for salon managers to prioritize pricing strategies and environmental aesthetics over service quality alone. Future research should consider broader age groups and include other psychological or experiential factors for a more comprehensive understanding of customer loyalty in the salon sector.